Pengaruh Penerapan Literasi Berbasis Web terhadap Peningkatan Minat Baca Peserta Didik Kelas V - Fitri Fitri; Triyo Supriyatno; Mohamad Zubad Nurul Yaqin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
In an all-digital era like today, the development of digital media and information technology poses challenges for users in accessing, selecting, and utilizing information from the times accompanied by digital developments which are expected to form a better increase in student learning. This study aims to determine the effect of implementing web-based literacy to increase students reading interest. This research uses quantitative methods with experimental research type, true experimental design. The results showed that there was an effect of implementing web-based literacy on increasing students reading interest, this was seen in the acquisition of a pretest score of 51.62 and an increase in the posttest score of 82.81 with a significant value of 0.000 < 0.05. After experiencing changes, it is seen that there is an increase in students reading interest, the application of web-based literacy will greatly help the effectiveness of learning and can also help students access the internet in more useful ways